2016
DOI: 10.5114/pg.2015.52589
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin, s-RANKL, and selected interleukins in the pathology of bone metabolism in patients with Crohn’s disease

Abstract: IntroductionCrohn's disease (CD) promotes the development of osteopaenia/osteoporosis, the cytokine background of which is not fully known.AimEvaluation of bone mineral density (BMD), the prevalence of osteopaenia and osteoporosis, and the determination of the levels of selected interleukins (IL), osteoprotegerin (OPG), and s-RANKL proteins in patients with CD in relation to a control group and assessment of the relationship between the tested cytokines, OPG, s-RANKL, and BMD.Material and methodsThirty-seven C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…Krela-Kaźmierczak I. et al showed that low OPG levels may be associated with osteoporosis in UC. Nevertheless, in CD patients increased RANKL levels were observed [ 20 , 21 ]. Interleukin 6 can modulate BMD via the OPG/sRANKL system in the femoral neck, which can cause a loss of bone, particularly in the course of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Krela-Kaźmierczak I. et al showed that low OPG levels may be associated with osteoporosis in UC. Nevertheless, in CD patients increased RANKL levels were observed [ 20 , 21 ]. Interleukin 6 can modulate BMD via the OPG/sRANKL system in the femoral neck, which can cause a loss of bone, particularly in the course of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, smoking might affect patients with CD and UC in different ways; it seems to protect against UC, whereas, on the other hand, it increases the risk of CD development [ 29 ]. As already mentioned, the RANK–RANKL–OPG pathway is considered a key element of osteoporosis pathogenesis among patients suffering from IBD [ 30 ]. Generally, inflammation and increased pro-inflammatory cytokines (i.e., IL-6, IL-1, IL-17, and TNF-α) affect RANKL production in IBD patients, thereby promoting osteoclastogenesis and bone resorption [ 28 , 31 ].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Stanisławowski et al [ 19 ] reported that patients with UC have higher local expression of serum OPG mRNA and protein than healthy participants[ 19 ]. Krela-Kaźmierczak et al [ 20 ] reported an increase in the OPG/RANKL ratio in CD patients[ 20 ]. According to a recent study, elevated osteocyte tumor necrosis factor (TNF)-α, interleukin (IL)-6, RANKL, and OPG correspond to higher osteoclast surfaces and a lower bone formation rate in an IBD model induced with dextran sodium sulfate[ 21 ].…”
Section: Introductionmentioning
confidence: 99%